2019
DOI: 10.1002/jcla.23085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of small dense low‐density lipoprotein concentration for predicting the risk of acute coronary syndrome in Chinese population

Abstract: Background Acute coronary syndrome (ACS) is the leading cause of death in developing and developed countries, yet assessing the risk of its development remains challenging. Several lines of evidence indicate that small, dense low‐density lipoproteins (sd‐LDL) are associated with increased cardiovascular disease risk. We aim to evaluate sd‐LDL concentration for predicting the risk of ACS in Chinese population. Methods Baseline characteristics of 121 patients with ACS and 172 healthy controls were obtained. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, ethnical variation, differing methodology, and varying cut-off points should be taken into consideration when attempting to compare precise sd-LDL levels [7][8][9]. Additionally, Wu et al [6] also exposed a gender effect. Sd-LDL levels were higher in males (0.71 ± 0.24 mmol/L) compared to females (0.63 ± 0.22 mmol/L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ethnical variation, differing methodology, and varying cut-off points should be taken into consideration when attempting to compare precise sd-LDL levels [7][8][9]. Additionally, Wu et al [6] also exposed a gender effect. Sd-LDL levels were higher in males (0.71 ± 0.24 mmol/L) compared to females (0.63 ± 0.22 mmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…Fukushima et al [ 5 ] showed higher sd-LDL levels for ACS patients (30 ± 14 mg/dL) compared to healthy controls (22 ± 8 mg/dL). Wu et al [ 6 ] observed higher sd-LDL levels for UA patients (male: 1.09 mmol/L and female: 1.03 mmol/L), STEMI patients (male: 1.30 mmol/L and female: 1.17 mmol/L), and NSTEMI patients (male: 1.44 mmol/L and female: 1.14 mmol/L) compared to healthy controls (male: 0.72 mmol/L and female: 0.62 mmol/L). These findings are suggestive of sd-LDL as a risk factor for ACS.…”
Section: Discussionmentioning
confidence: 99%
“…High LDL-C concentration in the serum is one of the major risk factors for coronary heart disease [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in different populations using various sdLDL measurements suggested that the sdLDL was related to the carotid intima thickness and in association with progression of carotid artery plaque [25][26][27]. Wu et al reported in 2019 that elevated sdLDL concentration was observed in ACS patients (n = 121) but not in healthy controls (n = 172) [28]. In ARIC study (11419 community-based participants and followed-up for 11 years), the plasma sdLDL was measured by an automated homogeneous assay.…”
Section: Discussionmentioning
confidence: 99%